Forage plants conserved - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Fodder plants and multipurpose trees that could hold the key to livestock production in Africa arc being collected by the International Livestock Centre for Africa (ILCA), which is anxious to conserve as many species as possible, otherwise some of...